Aesthetic treatment: Increased lower clinical crown (Research, Society and Development, 2021)
Currently the search for a perfect smile has been increasing and becoming a common requirement in clinical dental practice. This article has the objective to present a case report of a surgical aesthetic treatment for a patient with a excess gingiva of the lower teeth. Surgical crown augmentation surgery demonstrated a way to return the appropriate biological distances to restore health, function and aesthetics of the proposed case, providing satisfactory results for both the patient and the dentist.